Effect of High-Risk Human Papillomavirus but Normal Cytology at Test of Cure on Achieving Colposcopy Standards. Issue 2 (April 2018) - Kalampokas, Emmanouil; Wilson, Judith; Gurumurthy, Mahalakshmi; Cruickshank, Margaret E.
Abstract : Objective: In United Kingdom., test of cure after treatment of any grade of cervical intraepithelial neoplasia (CIN) incorporates high-risk human papillomavirus (Hr-HPV) test and cytology at 6-month follow-up. The aims of the study were to determine the rate of recurrent CIN in women who are Hr-HPV positive and cytology negative and to explore possible associated risk factors. Methods: A retrospective observational cohort study was performed in women treated for any grade CIN between 2010 and 2015 from a regional population, who were Hr-HPV positive and cytology negative at first follow-up. Results: A total of 2729 women were identified as treated for any grade CIN, and 213 (7.8%) were re-referred to colposcopy having Hr-HPV–positive test and negative cytology at test of cure. Their mean age was 31.56 years (range = 19–62 years). The mean time of follow-up per woman was 30.50 months (range = 2–63 months). At colposcopy, 171 (80.3%) had colposcopy examination only and 42 women (19.7%) had a biopsy. Twenty-four cases (11.3%) of CIN were identified of which 4 (1.9%) were CIN 2/3. Eleven women (5.2%) in total had a repeat treatment. Five women (2.3%) had biopsy-proven CIN 2/3 within 12-months after treatment. No cases of CIN 3+ after negative colposcopy were identified during the follow-up period. Conclusions: The incorporation of Hr-HPV testing yielded a very small number of women with residual CIN within 12 months of treatment. Our results suggest that women who are Hr-HPV positive and cytology negative after treatment of CIN with normal and adequate colposcopy could be discharged to routine recall if confirmed by larger national data.